Draft Genome Sequence of the Lignocellulose-Degrading Ascomycete Coniochaeta pulveracea CAB 683 - Borstlap, Cornelius Johannes (Microbiol Resour Announc, 2019)
Coniochaeta pulveracea is a soft-rot-causing ascomycete able to degrade lignocellulosic biomass. The first draft genome sequence of strain CAB 683 reported here has an estimated size of 30 Mb assembled into 852 scaffolds and 10,035 predicted protein-coding genes.